2019
DOI: 10.1371/journal.pgen.1008012
|View full text |Cite
|
Sign up to set email alerts
|

The CPEB translational regulator, Orb, functions together with Par proteins to polarize the Drosophila oocyte

Abstract: orb is a founding member of the CPEB family of translational regulators and is required at multiple steps during Drosophila oogenesis. Previous studies showed that orb is required during mid-oogenesis for the translation of the posterior/germline determinant oskar mRNA and the dorsal-ventral determinant gurken mRNA. Here, we report that orb also functions upstream of these axes determinants in the polarization of the microtubule network (MT). Prior to oskar and gurken translational activation, the oocyte MT ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 82 publications
0
5
0
Order By: Relevance
“…The functioning of the CPEB family proteins is essential at all stages of ontogeny. CPEBs play an important role in the formation and maintenance of cell polarity, participating in mRNA transport and localization, translational repression or activation of target mRNAs [ 30 , 81 83 ]. In the nervous system, this function is manifested in the participation of the CPEB proteins in neurogenesis and the functioning of neurons.…”
Section: Discussionmentioning
confidence: 99%
“…The functioning of the CPEB family proteins is essential at all stages of ontogeny. CPEBs play an important role in the formation and maintenance of cell polarity, participating in mRNA transport and localization, translational repression or activation of target mRNAs [ 30 , 81 83 ]. In the nervous system, this function is manifested in the participation of the CPEB proteins in neurogenesis and the functioning of neurons.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the literature CG17528 and Apc play important roles in regulating actin and microtubule cytoskeleton, while dop encodes a kinase that regulates protein localization and transport. 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 If Fat2 intracellular domain indeed interacts with these proteins, we imagine that Fat2 gathers the appropriate cytoskeletal effectors to regulate the cytoskeletal framing of axon terminals and thus affect axon behavior. We further investigated whether any of these genes genetically interacted with fat2 by asking if reducing the dose of fat2 by half in the ORN-specific RNAi knockdown background enhanced or suppressed phenotypes observed ( Figures 7 A and 7B).…”
Section: Resultsmentioning
confidence: 99%
“…The process of oocyte selection within such clusters is one of the key unresolved questions in oogenesis [ 9 , 13 , 14 ]. Recent studies in Drosophila revealed that oocyte selection is foreshadowed by autoregulated accumulation of oocyte-specific mRNA and proteins [ 16 , 19 , 20 , 23 , 33 ]. Even the simplest models of molecular and cellular processes in early stages of animal oogenesis contain a large number of parameters.…”
Section: Discussionmentioning
confidence: 99%